2006
DOI: 10.2353/ajpath.2006.050871
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Aspartic Proteinase-Like Gene Expressed in Stratified Epithelia and Squamous Cell Carcinoma of the Skin

Abstract: Homeostasis of stratified epithelia, such as the epidermis of the skin, is a sophisticated process that represents a tightly controlled balance between proliferation and differentiation. Alterations of this balance are associated with common human diseases including cancer. Here, we report the cloning of a novel cDNA sequence, from mouse back skin, that is induced by the phorbol ester 12-O-tetradecanoylphorbol-13-acetate (TPA) and codes for a hitherto unknown aspartic proteinase-like protein (Taps). Taps repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Although many investigators have considered that carcinogens such as ultraviolet rays, food additives, air pollution, etc. [8][9][10][11][12], induce multiple mutation steps in proto-oncogenes, there is an alternative possibility that such mutation is a process of glycolytic adaptation by living beings, namely, cancer cells. Hypothermia, hypoxia and hyperglycemia, which are induced by continuous stress (due to the lifestyle in patients), might be important factors which induce the adaptive response.…”
Section: Introductionmentioning
confidence: 99%
“…Although many investigators have considered that carcinogens such as ultraviolet rays, food additives, air pollution, etc. [8][9][10][11][12], induce multiple mutation steps in proto-oncogenes, there is an alternative possibility that such mutation is a process of glycolytic adaptation by living beings, namely, cancer cells. Hypothermia, hypoxia and hyperglycemia, which are induced by continuous stress (due to the lifestyle in patients), might be important factors which induce the adaptive response.…”
Section: Introductionmentioning
confidence: 99%
“…3,4). Recently, we applied global gene expression analysis on samples derived from distinct tumor stages and could identify a comprehensive list of novel tumor-associated genes (5)(6)(7)(8)(9)(10). One of the differentially expressed genes showing enhanced expression in advanced tumor stages encodes the brain and skin serine proteinase Bssp [also known as kallikrein 6 (Klk6) according to the recommendation for future nomenclature of kallikrein-related peptidases (11)].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are putative transmembrane domains in human and mouse SASPase, the full-length protein was not detected in epidermal lysates of human and mouse. It has also been demonstrated that mouse SASPase is found in the medium when the full-length protein was expressed in the HeLa cell line [ 60 ] . Thus, the function of the transmembrane domain of SASPase remains to be elucidated.…”
Section: Skin-specifi C and Sg-specifi C Protease Saspasementioning
confidence: 99%
“…Using high-throughput in situ hybridization screening, we have also identifi ed a mouse homolog of SASPase [ 35 ] as an SG-expressing gene. This protease has also been cloned as a 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced gene (Taps) from cDNA of mouse back skin epidermis [ 60 ] . Human and mouse SASPase/Asprv1/Taps were primarily expressed in skin and exclusively expressed in the SG of the epidermis ( Fig.…”
Section: Skin-specifi C and Sg-specifi C Protease Saspasementioning
confidence: 99%